Surfactant protein D (SP-D) alters cellular uptake of particles and nanoparticles. Issue 5 (August 2013) - Kendall, Michaela; Ding, Ping; Mackay, Rose-Marie; Deb, Roona; McKenzie, Zofi; Kendall, Kevin; Madsen, Jens; Clark, Howard
Abstract Surfactant protein D (SP-D) is primarily expressed in the lungs and modulates pro- and anti-inflammatory processes to toxic challenge, maintaining lung homeostasis. We investigated the interaction between NPs and SP-D and subsequent uptake by cells involved in lung immunity. Dynamic light scattering (DLS) and scanning electron microscopy (SEM) measured NP aggregation, particle size and charge in native human SP-D (NhSP-D) and recombinant fragment SP-D (rfhSP-D). SP-D aggregated NPs, especially following the addition of calcium. Immunohistochemical analysis of A549 epithelial cells investigated the co-localization of NPs and rfhSP-D. rfhSP-D enhanced the co-localisation of NPs to epithelial A549 cells in vitro. NP uptake by alveolar macrophages (AMs) and lung dendritic cells (LDCs) from C57BL/6 and SP-D knock-out mice were compared. AMs and LDCs showed decreased uptake of NPs in SP-D deficient mice compared to wild-type mice. These data confirmed an interaction between SP-D and NPs, and subsequent enhanced NP uptake.